The Use of Zwitterionic Methylmethacrylat Coated Silicone Inhibits Bacterial Adhesion and Biofilm Formation of Staphylococcus aureus - Woitschach, Franziska; Kloss, Marlen; Schlodder, Karsten; Rabes, Anne; Mörke, Caroline; Oschatz, Stefan; Senz, Volkmar; Borck, Alexander; Grabow, Niels; Reisinger, Emil Christian; Sombetzki, Martina (Frontiers in Bioengineering and Biotechnology, 2021)
In recent decades, biofilm-associated infections have become a major problem in many medical fields, leading to a high burden on patients and enormous costs for the healthcare system. Microbial infestations are caused by opportunistic pathogens which often enter the incision already during implantation. In the subsequently formed biofilm bacteria are protected from the hosts immune system and antibiotic action. Therefore, the development of modified, anti-microbial implant materials displays an indispensable task. Thermoplastic polyurethane (TPU) represents the state-of-the-art material in implant manufacturing. Due to the constantly growing areas of application and the associated necessary adjustments, the optimization of these materials is essential. In the present study, modified liquid silicone rubber (LSR) surfaces were compared with two of the most commonly used TPUs in terms of bacterial colonization and biofilm formation. The tests were conducted with the clinically relevant bacterial strains Staphylococcus aureus and Staphylococcus epidermidis. Crystal violet staining and scanning electron microscopy showed reduced adhesion of bacteria and thus biofilm formation on these new materials, suggesting that the investigated materials are promising candidates for implant manufacturing.